Nilai-Nilai Pendidikan dari Q.S. Al-Baqarah Ayat 152-153: Tentang Perintah Bersyukur dan Sabar - Mohamad Noer Amal; Ikin Asikin; Khambali (UNISBA Press, 2024)
Abstract. The focus of this research is to examine the values of Q.S. al-Baqarah verses 152-153: What is the opinion of the mufassir about Surah al-Baqarah verses 152-153? 2.What is the essence of Surah al-Baqarah verses 152-153 according to the commentators? 3.What is the concept of the commandment of gratitude and patience according to the experts? 4. What are the educational values of the commandments of gratitude and patience? From the results of this study, it can be concluded that these educational values are. Allah promises that by being grateful He will give pleasure to His servants, and by being patient, because patience can bring good, and Allah is with those who are patient. Servants who always perform dhikr (remembrance of Allah) in obedience to Allah, surely Allah will always remember His servants by giving rewards and forgiveness. (a) Every believer must be grateful and mention the name of Allah for sending the Messenger of Allah and his message (b) Withdrawal of blessings from those who deny the blessings that Allah gives (c) Patience and prayer are a help to believers (d) Good fortune to grateful and patient servants in the face of trials. Abstrak. Fokus penelitian ini mengkaji nilai-nilai tentang Q.S al-Baqarah Ayat 152-153: Tentang Perintah Syukur Dan Sabar.berdasarkan hasil tersebut maka terdapat rumusan masalah 1. Bagaimana pendapat mufassir tentang surat al-Baqarah ayat 152-153 ? 2.Bagaimana esensi dari surat al-Baqarah ayat 152-153 menurut ahli tafsir ? 3.Bagaimana konsep perintah syukur dan sabar menurut para ahli ? 4.Bagaimana nilai-nilai pendidikan tentang perintah syukur dan sabar ?. Hasil dari penelitian ini dapat disimpulkan bahwa nilai-nilai pendidikan ini adalah. Allah berjanji dengan bersyukur ia akan menambah kenikmatan kepada hambanya dan bersabarlah karena kesabaran dapat membawa kebaikan, sesungguhnya Allah bersama orang-orang yang sabar. Hamba yang selalu melaksanakan ketatan kepada Allah berdzikir (mengingat Allah) niscaya Allah akan selalu menginat hamba-Nya dengan memberi pahala dan ampunan. (a.Setiap mukmin wajib bersyukur dan menyebut asma Allah karena telah mengutus rasulullah dan risalahnya (b.Pencabutan nikmat bagi orang-orang yang ingkar terhadap nikmat yang Allah berikan (c. Sabar dan shalat merupakan pertolongan untuk orang beriman (d.Kebahagian kepada hamba yang bersyukur dan sabar dalam mengahdapi cobaan.